Lafaz Mujmal Nafkah dalam Al-Qurʾān dan Operasionalisasinya dalam Pasal 80 KHI: Analisis Dilālah al-Alfāẓ terhadap Kewajiban Nafkah Suami bagi Istri yang Bekerja - Ridwan, Iwan; Mohamad Athoillah; Ali Khosim (Rayah Al-Islam, 2026)
This study examines the mujmal (ambiguous) expressions in Quranic verses on spousal maintenance (nafkah) and analyzes their operationalization within Article 80 of the Compilation of Islamic Law (KHI) through the dalālah al-alfāẓ theory in uṣūl al-fiqh. Expressions such as bil-maʿrūf (Q.S. al-Baqarah: 233), min wujdikum, and min saʿatihi (Q.S. al-Ṭalāq: 6–7) are mujmal expressions that do not definitively prescribe the quantum of maintenance, thus requiring bayān from the Sunnah and scholarly ijtihad. Using a qualitative library-research method with a normative-analytical approach, the study finds: (1) the husband's maintenance obligation is absolute according to the dalālah ʿibārah of Q.S. al-Baqarah: 233, independent of the wife's economic status; (2) a working wife's income is her exclusive property and does not reduce her maintenance entitlement; and (3) Article 80 KHI constitutes a codification of bayān over these mujmal expressions but leaves a legal gap regarding working wives requiring resolution through maqāṣid al-sharīʿah-based ijtihad. The study proposes a three-component normative framework integrating dalālah analysis, maqāṣid principles, and positive Indonesian law.